Adverse events secondary to cetuximab therapy in head & neck cancer therapy and risk factors for serious outcomes. (August 2022) - Stanbouly, Dani; Philipone, Elizabeth; Morlandt, Anthony B.; Kaleem, Arshad; Chuang, Sung-Kiang; Patel, Neel
Abstract: Objectives: The objective of this study is to illustrate the adverse events secondary to cetuximab therapy for head and neck cancer and elucidate risk factors for serious outcomes. Materials and methods: This retrospective study was conducted using the FDA Adverse Event Reporting System (FAERS). The predictor variables were patient characteristics, country of treatment, and adverse events. The outcome variable was the rate of serious outcomes. Multivariate logistic regression was created to identify all significant risk factors of the outcome. P < 0.05 was considered statistically significant. Results: The final sample consisted of 3, 086 reports of adverse events from cetuximab therapy in head and neck cancer treatment, of which 2, 746 reports were considered serious (89.0%) per the FAERS criteria. Mucosal inflammation was the most common adverse event. The strongest risk factor for a serious outcome was cetuximab therapy in countries outside the US (OR 105.2, P < 0.01). Polytherapy (OR 7.6, P < 0.01) was also a risk factor for serious outcome. Conclusions: Health-care providers should be aware of potential complications following cetuximab administration, particularly when administered in countries outside the US and in conjunction with other medications.